2011
DOI: 10.3389/fnbeh.2011.00045
|View full text |Cite
|
Sign up to set email alerts
|

Cell Signaling Underlying Epileptic Behavior

Abstract: Epilepsy is a complex disease, characterized by the repeated occurrence of bursts of electrical activity (seizures) in specific brain areas. The behavioral outcome of seizure events strongly depends on the brain regions that are affected by overactivity. Here we review the intracellular signaling pathways involved in the generation of seizures in epileptogenic areas. Pathways activated by modulatory neurotransmitters (dopamine, norepinephrine, and serotonin), involving the activation of extracellular-regulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 165 publications
(207 reference statements)
1
59
0
Order By: Relevance
“…These markers have been found to be widely expressed in the hippocampus of animals exposed to seizures induced by kainate (Kim et al, 1994; Crespo-Biel et al, 2007), pilocarpine (Garrido et al, 1998; Berkeley et al, 2002; Houser et al, 2008), bicuculline (Gass et al, 1993; Ben et al, 2014), and dopamine D 1 receptor agonists (Bozzi et al, 2011; Gangarossa et al, 2011, 2014; Bozzi and Borrelli, 2013). We also found p-ERK1/2 to be induced by audiogenic seizures in mice affected by fragile X syndrome (Curia et al, 2013) and, interestingly, changes in p-ERK1/2 have been associated to a different sensitivity to proconvulsant stimuli (Glazova et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These markers have been found to be widely expressed in the hippocampus of animals exposed to seizures induced by kainate (Kim et al, 1994; Crespo-Biel et al, 2007), pilocarpine (Garrido et al, 1998; Berkeley et al, 2002; Houser et al, 2008), bicuculline (Gass et al, 1993; Ben et al, 2014), and dopamine D 1 receptor agonists (Bozzi et al, 2011; Gangarossa et al, 2011, 2014; Bozzi and Borrelli, 2013). We also found p-ERK1/2 to be induced by audiogenic seizures in mice affected by fragile X syndrome (Curia et al, 2013) and, interestingly, changes in p-ERK1/2 have been associated to a different sensitivity to proconvulsant stimuli (Glazova et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The AKT1 gene is an attractive candidate because it codes for a protein kinase that forms an integral part of the dopamine receptor signaling cascade in the striatum (9). Moreover, in vivo administration to mice of delta-9-tetrahydrocannabinol (delta-9-TCH), the active ingredient in cannabis, activates this signaling cascade via AKT1 phosphorylation (10,11).…”
mentioning
confidence: 99%
“…The prototypical and most characterized immediate early gene-encoded transcription factor is c-Fos which is expressed with a peak of 30 to 90 minutes after stimulation (Herrera and Robertson, 1996). There is ample literature describing neuronal c-Fos induction following kindling and other seizure models (Barone et al, 1993; Bozzi et al, 2011; Chiasson et al, 1995; Dragunow and Faull, 1989; Dragunow and Robertson, 1988; Morgan and Curran, 1991a, b; Motte et al, 1997). Furthermore, several studies have demonstrated a correlation between the expansion of c-Fos induction from limbic areas to the cerebral cortex and the progression of epileptic seizures (Andre et al, 1998; Clark et al, 1991; Ebert and Loscher, 1995; Hiscock et al, 2001; Simler et al, 1999; Szyndler et al, 2009; Willoughby et al, 1997).…”
Section: Discussionmentioning
confidence: 99%